Psychological distress in adults with congenital heart disease: focus beyond depression. (30th January 2019) - Gleason, Lacey P.; Deng, Lisa X.; Khan, Abigail M.; Drajpuch, David; Fuller, Stephanie; Ludmir, Jonathan; Mascio, Christopher E.; Partington, Sara L.; Tobin, Lynda; Kim, Yuli Y.; Kovacs, Adrienne H.
Abstract: Background: Adults with congenital heart disease face psychological challenges although an understanding of depression vs. anxiety symptoms is unclear. We analyzed the prevalence of elevated symptoms of anxiety and depression and explored associations with demographic and medical factors as well as quality of life. Methods: Adults with congenital heart disease enrolled from an outpatient clinic completed the Hospital Anxiety and Depression Scale and two measures of quality of life: the Linear Analogue Scale and the Satisfaction with Life Scale. Medical data were obtained by chart review. Results: Of 130 patients (median age = 32 years; 55% female), 55 (42%) had elevated anxiety symptoms and 16 (12%) had elevated depression symptoms on subscales of the Hospital Anxiety and Depression Scale. Most patients with elevated depression symptoms also had elevated anxiety symptoms (15/16; 94%). Of 56 patients with at least one elevated subscale, 37 (66%) were not receiving mental health treatment. Compared to patients with 0 or 1 elevated subscales, patients with elevations in both (n=15) were less likely to be studying or working (47% vs. 81%; p =0.016) and reported lower scores on the Linear Analogue Scale (60 vs. 81, p <0.001) and the Satisfaction with Life Scale (14 vs. 28, p <0.001). Conclusions: Among adults with congenital heart disease, elevated anxiety symptoms are common and typically accompany elevated depressive symptoms. The combination is associated with unemployment and lower quality of life. Improved strategies to provide psychosocial care and support appropriate engagement in employment are required.